Relationships Between Rapid Urbanization and Extreme Summer Precipitation Over the Sichuan–Chongqing Area of China - Wang, Hao; Yan, Yilin; Long, Keji; Chen, Qingqing; Fan, Xingang; Zhang, Fugui; Tan, Linyin (Frontiers in Earth Science, 2022)
China has undergone rapid urbanization over the past few decades and, accordingly, changes have occurred in the extreme precipitation events. However, few studies have focused on the relationships between rapid urbanization and extreme precipitation events in southwest China, particularly in the Sichuan–Chongqing area, which has a complex topography and has experienced rapid urbanization over the past few decades. This is the first study to analyze the impact of urbanization on the amount, frequency, and intensity of extreme summer (June–August) precipitation events over the past 30 years. Our results indicate that extreme precipitation events primarily occurred in the urban-dominated Sichuan Basin, particularly during the fast urbanization development stage (FUDS) of 1994–2015. Extreme precipitation amounts and intensities increased during the FUDS, implying the greater probability of individual precipitation events developing into heavy or extreme events in a particular area. In addition, the probability distribution functions of the occurrence and volume of strong convective events significantly increased during the FUDS. Lastly, the annual increase in urban-scale land surface air temperature, increase in wet convection, and changes in wind speed are identified as essential factors leading to extreme precipitation events in this region.